Association of CHA2DS2-VASc Score with Post Cardiac Surgery Atrial Fibrillation: A Single Centre Study - Waqas Alam; Syed Aqeel Hussain; Rehan Masroor; Syed Muzaffar Hasan Kirmani; Muhammad Ali; Fahd Ur Rehman; Rehana Javaid; Hafsa Khalil (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the association of CHA2DS2-VASc score with postoperative atrial fibrillation in cardiac surgery patients.